2017
DOI: 10.1021/acs.chemmater.7b00046
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis and Flexible Self-Assembly of Monodisperse Au@Semiconductor Core/Shell Hetero-Nanocrystals into Diverse Superstructures

Abstract: Monodisperse nonepitaxially grown Au@MX (MX = Ag 2 S, ZnS, or CdS) core/shell hetero-nanocrystals (HNCs) with controlled crystallinity, composition, anisotropically shaped Au cores but isotropic overall morphologies were successfully prepared. By using C18 acid/alkali co-capping surface ligands, the as-prepared Au@MX HNCs can selfassemble into large-scale two-dimensional monolayer and three-dimensional multilayer superlattices (SLs) on both flexible (graphene) and rigid (Si wafer or glass) substrates. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 43 publications
0
52
1
Order By: Relevance
“…Suib et al reported an inverse micelle synthesis system to prepare mesoporous metal oxides 14 . Mesoporous materials with diverse morphologies and tunable pore sizes have been prepared by controlling the synthesis conditions and the properties of the template molecules based on soft templating 15,16 . This approach is flexible and effective for largescale synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Suib et al reported an inverse micelle synthesis system to prepare mesoporous metal oxides 14 . Mesoporous materials with diverse morphologies and tunable pore sizes have been prepared by controlling the synthesis conditions and the properties of the template molecules based on soft templating 15,16 . This approach is flexible and effective for largescale synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, its wide band gap and high recombination rate of photo-generated charges often lead to low quantum yield in the photocatalytic reactions. To address the key issue of low quantum yield, many methods, such as noble metal deposition 7,8 , element doping 9 and semiconductor coupling 10,11 , have been extensively studied and applied in recent years 1215 . Among these approaches, coupling with other semiconductors for forming the composites is one of the most effective ways to improve the separation efficiency of photo-generated charges, which could also take full advantage of solar spectrum, compared with the individual material 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Interface, formed between two different phases, can provide interfacial interactions for application ranging from chemical synthesis of shaped controlled NCs to self‐assembly of NCs to be SLs . For example, noble metal NCs, semiconductor NCs, as well as the nonepitaxial growth core/shell NCs can be assembled into monolayer SLs, multilayer SLs, and even binary NCs SLs by the aid of the interfaces . Among these SLs, due to the SPR effect of Au NCs, the Au‐based SLs might react with the SPR‐related light that leads to the hot spots generation.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the existence of strong SPR effect from Au core, the hot spots may be generated at the interparticle gaps within the core/shell NCs assembly by the 532 nm laser irradiation. The monodisperse Au@CdS NCs were synthesized by our published nonepitaxial strategy and the SLs monolayer could be obtained and deposited onto the carbon substrates by a dip‐coating method …”
Section: Resultsmentioning
confidence: 99%